KAJIAN METODA PERENCANAAN TEBAL LAPIS TAMBAH PERKERASAN LENTUR - Nyoman Suaryana; Yohanes Ronny Priyo Anggodo (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
RDS (Roadworks Design System) is a method to Design overlay flexible pavement and currently used by the Design and Supervison of Road and Bridge Construction (P2JJ). The method adoptic the design method which was firstly developed by DR Ray Millard. 1983 and DR Paterson. 1985. In recent years, many methods have been developed, such as AUSTROADS, 1992, Asphalt Institute MS-17, 2000 and Pusat Litbang Jalan dan Jembatan in 2005 also has released a guide to the structural design of road pavement based on deflection, Pd T-05-2005-B, 2005. From some methods mentioned above, it was found that a significant difference in the result of the overlay thickness designed. Some factors influencing are deferences in the traffic loading calculation, method in abtaining a represenative deflection (grouping an uniform deflection) and environmental factors. Principally, overlay thickness should meet two fatique criteria i.e. permanent deformation and fatique performance. Both criteria should be taken into account in calculating overlay thickness as shown in Austroads design procedure. Key words : Significant differences, Traffic volume, Deflection uniformity, Environmental factors.